ENINGKATAN KINERJA ADMINISTRASI PENJUALAN CHEMICAL WATER TREATMENT PRODUCT DENGAN PEMANFAATAN SISTEM INFORMASI - Maimunah Maimunah; Berkat Jaya Batee; Mega Agustina Margareta (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2017)
The use of computers and systems has become a major requirement in order to improve the performance of a company. Wastewater treatment company is a company engaged in the sale of chemical water treatment product. Where in the data processing is done manually consequentlyoften occur problems such as the same numbering with other invoices that result in errors in the manufacture of sales reports of goods, has not fulfilled the administrative control system and sales reports. In this study using MySQL for database management which can store all sales reports and present accurate data, and generate timely reports in accordance with the desired needs. All data related to the sales report system will be well stored and the results are more accurate. PHP is a programming language used for the design of proposed programs and Dreamweaver as a tool making program.